(untitled) (Herald of Journalism, 2018)
The author submits the review essay, devoted to the new book of the famous Kazakhstan writer, member of Academy of journalism of Kazakhstan, the editor of «The Kazakhstan truth» Alexander Tarakov. «The Kazakhstan character» - the book of sketches dated for anniversary of independence of the country includes three chapters «Virgin guard», «Vozrashcheniye to heroes», «Professionals» also represents the collection of sketches about the modern heroes, fighters capable to refract fatal circumstances, the true patriots forming a quintessence of the concept «Kazakhstan character».